Implementasi Pendekatan Saintifik pada Pembelajaran Daring Selama Masa Pandemi Covid-19 di Lembaga Pendidikan Dasar - Ahmad Izzuddin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
The impact of the Covid-19 pandemic is felt at all levels of education, from elementary to higher education. The existence of this pandemic has become a challenge for educators to innovate in developing and implementing lesson plans that have been prepared previously. One of the learning approaches used is the scientific approach. This approach trains students to learn with the scientific method through the process of observing, asking questions, gathering information, experimenting, associating and communicating the material they are learning. This is where the ability of a teacher is required to be creative in integrating the steps of the scientific approach with online methods. During the past year, the implementation of a scientific approach in online learning during the Covid-19 pandemic has been carried out in basic education institutions with quite good results. Some of the advantages of the scientific approach using online learning include (1) the dependence of students on educators is slightly reduced because learning is carried out more at home through the network (online) (2) the flexibility of time and place to take the steps of the scientific approach to be a separate experience for students (3 ) train students to use learning technology from an early age. The weaknesses of online learning include (1) internet signal/connection is not very stable (2) teacher and student interactions cannot interact directly (3) still lack of facilities and infrastructure in the implementation of online learning (4) inadequate parental supervision This causes students to often lose focus in learning.